Laws Relating to Corporate Environmental Crimes in India: A Critical Analysis - Mahima Kwatra Dr. Mudassir Nazir (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
India's swift industrialization and economic expansion have resulted in environmental issues, primarily attributable to corporate activity. These firms frequently engage in illicit and detrimental activities such as the release of untreated garbage, air pollution, deforestation, and inadequate management of hazardous materials, resulting in significant environmental degradation and health hazards for local residents. India has implemented various environmental statutes designed to regulate corporate activities and mitigate their effects. This paper rigorously analyzes the principal legislative frameworks, including the Environment (Protection) Act of 1986, the Air (Prevention and Control of Pollution) Act of 1981, and the Water (Prevention and Control of Pollution) Act of 1974, emphasizing their efficacy, enforcement mechanisms, and constraints. Judicial interventions and public participation are crucial in addressing these concerns, impacting the efficacy of these legislation. The investigation identifies systemic deficiencies and obstacles, such as insufficient enforcement, regulatory corruption, and restricted community engagement. The study closes by recommending actions to fortify the legal framework, improve regulatory enforcement, and encourage sustainable corporate practices in India.